The closure of the Brazilian-Venezuelan border during the covid-19 pandemic: international law analysis of ordinance no. 120 of March 2020 / O fechamento da fronteira do Brasil com a Venezuela em resposta à pandemia do covid-19: análise da portaria nº120 de 17 de março de 2020 com base no direito internacional - Nascimento, Luiz Sales do; Lapa, Rosilandy Carina Candido; Mendes, Victor Augusto; Reis, Vanessa Vasques Assis dos (Revista Direito e Práxis, 2023)
DOI: 10.1590/2179-8966/2021/62332. Abstract This study investigates how Regulatory Ordinance No. 120 of March 17, 2020, reflects the constitutional principles and international treaties recognized by Brazil. This Ordinance is a non-statutory regulation to fight COVID-19 seeking to prohibit the entry of people from Venezuela during this pandemic. This deductive investigation assumes that this measure is not supported by the national and international migration laws incorporated by Brazil. The legal justifications the act used as arguments were found to be inconsistent with the formal requirements for the act itself as per the Brazilian legal framework. Verification of its legal and technical justifications showed a lack of legal, scientific, and empirical support, turning the Ordinance into a target of criticism by Civil Society organizations. In light of national and international law, the analyzed instrument can be considered in breach of international technical guidelines for administering vulnerable migrant influxes as is the case of Venezuelans in Brazil. Keywords: COVID-19; Refugees; Venezuela; Borders; Forced migrants. Resumo Este estudo tem como objetivo investigar como a Portaria nº 120, de 17 de março de 2020 reflete os princípios constitucionais e tratados internacionais reconhecidos pelo Brasil. A presente portaria é apresentada como medida infralegal de combate ao COVID-19 buscando proibir o ingresso de pessoas oriundas da Venezuela. A investigação dedutiva parte do pressuposto de que a portaria não se sustentaria frente às legislações migratórias nacionais e internacionais incorporadas pelo Brasil. Constatou-se que as justificativas legais apresentadas pelo ato infralegal apresentara inconsistências com as exigências formais para o referido ato. Verificou-se que as justificativas jurídicas e técnicas apresentadas pela portaria carecem de lastro legal, científico e empírico, tornando a medida alvo de críticas pela sociedade civil. Considerou-se que, frente ao direito nacional e internacional, o fechamento realizado pelo instrumento infralegal analisado vai de encontro às orientações técnicas para administração de fluxos de migrantes vulneráveis, que incluem Venezuelanos no Brasil. Palavras-chave: COVID-19; Refugiados; Venezuela; Fronteiras; Migrantes forçados.